Exploring Latino male graduates' awareness of degree value and its influence on community college enrollment decisions - Ramos, Cynthia (My University, 2026)
Recent U.S. Census data indicate that the Hispanic/Latino population continues to grow, comprising approximately 19.5% of the U.S. population in 2023, with projections estimating this group will make up nearly 28% of the population by 2060. Given the significant growth of the Hispanic and Latino population, and the ongoing influence and impact they stand to have on the communities they live in, it is critical to continue exploring and examining the factors influencing Latino male higher education attainment. Currently, Latino males have drastically lower levels of educational attainment than other males. If Latino males continue to maintain low educational attainment rates and are underrepresented in high-wage jobs, the ability of the community to advance socioeconomically is severely limited. This study explored how perceptions of degree value are formed and how they influence students’ choices to enroll and persist. An explanatory sequential mixed-methods design was used to discover participants’ awareness of degree value. Results revealed insights from data collection, surveys, and focus groups and interviews on the factors influencing Latino males' perceived value of community college education.
Keywords: Latino males; Hispanic; Community college; Degree value; Degree utility; Motivation